Anthropogenic and Hydroclimatic Controls on the CO2 and CH4 Dynamics in Subtropical Monsoon Rivers - Shuai Chen; Lishan Ran; Clément Duvert; Boyi Liu; Yongli Zhou; Xiankun Yang; Qianqian Yang; Yuxin Li; Si‐Liang Li (Water Resources Research)
Abstract Anthropogenic perturbations have substantially altered riverine carbon cycling worldwide, exerting influences on dissolved carbon dioxide (CO2) and methane (CH4) dynamics at multiple levels. However, the magnitude and role of anthropogenic activities in modulating carbon emissions across entire river networks, as well as the influence of climatic controls, remain largely unresolved. Here, we explore the controlling factors of riverine CO2 and CH4 dynamics across 62 subtropical, monsoon‐influenced streams and rivers through basin‐wide seasonal measurements. We found that land use and aquatic metabolism played significant roles in regulating the spatial and temporal patterns of both gases. Increased nutrient levels and organic matter contributed to higher partial pressure of CO2 (pCO2) and CH4 (pCH4). Dissolved oxygen, stable carbon isotope of dissolved inorganic carbon, the proportion of impervious surface, catchment slope, and river width were the major predictors for pCO2. For pCH4, the major predictors were Chlorophyll a and water temperature, which influence organic matter availability and methanogenesis. Seasonal variations in pCO2 and pCH4 were strongly modulated by hydroclimatic conditions, with temperature markedly regulating river ecosystem metabolism. These findings highlight the likelihood of significant changes in riverine carbon emissions as climate changes and land use patterns evolve, thereby profoundly affecting the global carbon cycle.